共役点オーロラ画像処理システムの開発 - 港屋, 浩一; ミナトヤ, ヒロカズ; Minatoya, Hirokazu; 小野, 高幸; オノ, タカユキ; Ono, Takayuki; 佐藤, 夏雄; サトウ, ナツオ; Sato, Natsuo; 巻田, 和男; マキタ, カズオ; Makita, Kazuo; et al. (国立極地研究所, 1994)
オーロラの位置, 形および動きに関する南北共役性の解析を行うためにオーロラ画像処理システムの開発を行った。本システムは以下の3点で重要な特徴をもっている。1)本システムにより, 大量の画像データを高速かつ効率的に解析できる。2)磁気座標展開図およびオーロラダイナミック表示図により, オーロラの位置, 形および動きに関する南北比較が容易である。3)昭和基地とあすか基地の画像を合成することにより広範囲のオーロラ像を確認することができる。本システムを用いた実データ解析として, 1991年9月9日～10日, 昭和基地, あすか基地, Husafellの3点同時に観測されたSITオーロラTVカメラデータに適用してみた。 An image data processing system has been developed in order to analyze auroral conjugacy of auroral positions, shapes and motions. The new system has the following advantages : 1) A large amount of image data can be quickly and efficiently analyzed by using the system. 2) The geomagnetic coordinate display and auroral dynamic display produced by the system are useful for comparison of auroral positions, shapes and motions between two hemispheres. 3) The smooth combination techniques of auroral image data make it possible to investigate auroral conjugacy with wider field of view than that of one station. The developed processing system is applied to conjugate auroral TV camera data of September 9-10,1991 events observed at Syowa and Asuka stations, in Antarctica and Husafell in Iceland. departmental bulletin paper